2009
DOI: 10.1073/pnas.0904691106
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the evolution of extant and extinct ruminants with high-throughput phylogenomics

Abstract: The Pecorans (higher ruminants) are believed to have rapidly speciated in the Mid-Eocene, resulting in five distinct extant families: Antilocapridae, Giraffidae, Moschidae, Cervidae, and Bovidae. Due to the rapid radiation, the Pecoran phylogeny has proven difficult to resolve, and 11 of the 15 possible rooted phylogenies describing ancestral relationships among the Antilocapridae, Giraffidae, Cervidae, and Bovidae have each been argued as representations of the true phylogeny. Here we demonstrate that a genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
216
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(250 citation statements)
references
References 31 publications
28
216
0
2
Order By: Relevance
“…Previous studies have demonstrated that robust phylogenetic signal can be obtained by querying domestic animal SNP arrays with DNA from related species of the same genus, family, or order, despite having diverged tens of millions of years from the array reference genome (Decker et al 2009;McCue et al 2012). Here, we generated genome-wide SNP data from 38 cat species and analyzed these separately and together with Y-linked variation and whole mitogenomes, allowing us to disentangle different maternal, paternal, and biparental histories within a diverse family of mammals.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that robust phylogenetic signal can be obtained by querying domestic animal SNP arrays with DNA from related species of the same genus, family, or order, despite having diverged tens of millions of years from the array reference genome (Decker et al 2009;McCue et al 2012). Here, we generated genome-wide SNP data from 38 cat species and analyzed these separately and together with Y-linked variation and whole mitogenomes, allowing us to disentangle different maternal, paternal, and biparental histories within a diverse family of mammals.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…To demonstrate that a potential bias of nucleotide identification caused by the two-dye Illumina genotyping system on nondomestic cat species did not influence phylogenetic accuracy, we also performed a second phylogenetic analysis in which the nuclear SNP matrix was translated into a binary matrix ("0" representing G or C; "1" representing A or T), following Decker et al (2009).…”
Section: Snp Genotyping and Analysismentioning
confidence: 99%
“…Moreover, the five studied beef breeds have diverged genetically during their phylogenetic history. Charolais and Limousin are continental French breeds, Hereford and Angus are of British origin, and Simmental originated from Switzerland (Decker et al, 2009). In breeds with low muscularity and high fat deposition (especially Hereford), high fat levels are more strongly genetically connected to heavier carcasses and high muscularity.…”
Section: Trait Variationmentioning
confidence: 99%
“…Given the close interaction of humans with domesticated species and the economic importance of domesticated organisms, it is not surprising that humans have developed many of these species as model organisms. Over the last few years, genomic data have been used to reconstruct the domestication history of many of these species, including dogs (1, 2), horses (3), sheep (4), and cattle (5,6). The global economic importance of cattle, in combination with the anthropological interest in the shared history of cattle and humans over the last 10,000 y, makes cattle an ideal target for spatial genetic research.…”
mentioning
confidence: 99%